Analysing institutions, policies, & farming systems for sustainable agriculture in Central and Eastern European countries in transition - Franz Gatzweiler; Timo Sipiläinen; Stefan Bäckman; Anett Zellei (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2001)
The aim of this paper is to develop a comprehensive conceptual framework for the analysis of institutions, policies and farming systems for agri-environmental sustainability in Central and Eastern European countries in transition. The basic unit of analysis is the 'agri-environmental action scenario'. The action scenario consists of a set of components which together shape the outcomes of an agri-environnmental action situation. The framework consists of 1) the environmental effects of transition, 2) policies, 3) institutions, and 4) farming systems. We aim at characterising these key elements of the framework, their relationship and interactions, and their role in achieving sustainability at the interface between agriculture and the environment. Environmental areas of concern are: water, soil and biodiversity. The paper intends to create a common understanding of basic concepts and a shared conceptual model among the members of the Central and Eastern European Sustainable Agriculture (CEESA) Network. The framework will be adapted according to new insights and findings during the course of research activities of the CEESA research project.
Keywords: 330; Landwirtschaft; Nachhaltige Entwicklung; Agrarverfassung; Osteuropa